Cardiomyocyte-specific PCSK9 deficiency compromises mitochondrial bioenergetics and heart function - Laudette Marion; Lindbom Malin; Arif Muhammad; Cinato Mathieu; Ruiz Mario; Doran Stephen; Miljanovic Azra; Rutberg Mikael; Andersson Linda; Klevstig Martina; Henricsson Marcus; Bergh Per-Olof; et al. (OXFORD UNIV PRESS, 2025)
Aims: Pro-protein convertase subtilisin-kexin type 9 (PCSK9), which is expressed mainly in the liver and at low levels in the heart, regulates cholesterol levels by directing low-density lipoprotein receptors to degradation. Studies to determine the role of PCSK9 in the heart are complicated by the close link between cardiac function and systemic lipid metabolism. Here, we sought to elucidate the function of PCSK9 specifically in the heart by generating and analysing mice with cardiomyocyte-specific Pcsk9 deficiency (CM-Pcsk9(-/-) mice) and by silencing Pcsk9 acutely in a cell culture model of adult cardiomyocyte-like cells.
Methods and results: Mice with cardiomyocyte-specific deletion of Pcsk9 had reduced contractile capacity, impaired cardiac function, and left ventricular dilatation at 28 weeks of age and died prematurely. Transcriptomic analyses revealed alterations of signalling pathways linked to cardiomyopathy and energy metabolism in hearts from CM-Pcsk9(-/-) mice vs. wild-type littermates. In agreement, levels of genes and proteins involved in mitochondrial metabolism were reduced in CM-Pcsk9(-/-) hearts. By using a Seahorse flux analyser, we showed that mitochondrial but not glycolytic function was impaired in cardiomyocytes from CM-Pcsk9(-/-) mice. We further showed that assembly and activity of electron transport chain (ETC) complexes were altered in isolated mitochondria from CM-Pcsk9(-/-) mice. Circulating lipid levels were unchanged in CM-Pcsk9(-/-) mice, but the lipid composition of mitochondrial membranes was altered. In addition, cardiomyocytes from CM-Pcsk9(-/-) mice had an increased number of mitochondria-endoplasmic reticulum contacts and alterations in the morphology of cristae, the physical location of the ETC complexes. We also showed that acute Pcsk9 silencing in adult cardiomyocyte-like cells reduced the activity of ETC complexes and impaired mitochondrial metabolism.
Conclusion: PCSK9, despite its low expression in cardiomyocytes, contributes to cardiac metabolic function, and PCSK9 deficiency in cardiomyocytes is linked to cardiomyopathy, impaired heart function, and compromised energy production.